KELOMPOK ISLAM NURCU DAN NEGARA: PENERIMAAN MUSLIM ATAS SEKULARISME - Khamami, Akhmad Rizqon (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This article explores the Nurcu's response to the implementation of secularization in the Republic of Turkey in the 20th century. The implementation of secularism in Turkey brought about three groups: Kemalists, Islamists, and Nurcu. While the Kemalists became the main proponents of secularism, and the Islamists strongly rejected it, a third group emerged, that is the Nurcu. The Nurcu is an association of followers of the teachings of Said Nursi, a Turkish scholar and thinker. This article assumes that the Nurcu accepts secularism, and actually supports it. They believe that secularization is not in contradiction to Islamic teachings. The acceptance of secularism subsequently leads the Nurcu's responses to state, democracy, role of the people, and the economic system adopted by the state. This study found that the Nurcu group enjoyed social and political openness, democracy and economic liberalization in Turkey, despite tensions between the Nurcu and the Kemalist.